C3 mutations and poor pegcetacoplan response in paroxysmal nocturnal hemoglobinuria - Rodríguez de Córdoba, Santiago; Reparaz Suevos, Andrea; González Sanz, Silvia; Fernández, Francisco J.; Vega, M. Cristina; Varela, Enrique Colado; Lada Colunga, Alejandro; Vallejo Llamas, Juan Carlos; Gonzalez-Rodríguez, Ana Pilar (Frontiers in Immunology, 2025)
IntroductionParoxysmal nocturnal hemoglobinuria (PNH) is treated with complement inhibitors, yet incomplete responses remain a challenge. Terminal inhibition with eculizumab prevents intravascular hemolysis but often leaves residual extravascular hemolysis, while proximal inhibitors such as pegcetacoplan mitigate extravascular hemolysis though intravascular hemolysis may persist. Understanding resistance mechanisms is critical to guide therapy.MethodsWe report a PNH patient with incomplete responses to both eculizumab and pegcetacoplan. Genetic analysis revealed a mutation in the C3 MG-ring. Functional assays assessed the effects of this variant on C3b inactivation by complement regulators and on pegcetacoplan binding. Additional MG-ring variants were analyzed to explore broader relevance.ResultsThe C3 MG-ring mutation rendered C3b resistant to inactivation and reduced pegcetacoplan binding, explaining persistent hemolysis under both therapeutic approaches. Other MG-ring variants produced similar effects, indicating that this structural domain represents a recurrent vulnerability of C3 and a potential mechanism of resistance to complement inhibition.DiscussionThese findings show that C3 MG-ring mutations can undermine both terminal and proximal complement inhibitors, directly impacting treatment efficacy in PNH. Complement genetic testing, combined with functional readouts, may help identify patients at risk of suboptimal responses and support personalized therapeutic strategies.